(3af GdLRGFQ jJcde GdSdGM (B:s (3fVGd TYH ef CLd GdJMQjQ (B/s - (3HQHSJjQ,Gjag s; (3cMjd(B,(3YHO Gddg as ((3GdLRGFQ (B:s (3GdeDSSI GdLRGFQjI ddWHGYI ,s, 1989)
(3GfJgi Yed gPG GdcJGH aj BPGQ fI (B1959(3h gh jYO JMdjdG TGedG dfVGd GdTYH GdLRGFQj h gPG Mb hhGLH Sjbhe Hg GdTYH GdLRGFQj faSg aj CMO GdGjGe QHeG HYO Cf jJecf eDQNhg h COHG Dg HYO Cf jdbhG GdSdGM ef GjOjge ddJaQZ ddcJGHI h gPG GdcJGH gh eMGhdI dJhVjM HYV GdGehQ ddfGS aj ChQHG Yf GdLRGFQ GdJj dG jYQa GdcKjQhf YfgG dGd Gdbdjd djS abW Yf GdLRGFQ GdabjQI h GdeYPHI Hd CjVG Yf GdLRGFQ GdHWdI h GdJj JcJH HGdOe h GdOehY UaMGJ JGQjN h eSJbHd eTQa (B.s
Keywords: (3GdLRGFQ s; (3GdSdGM s; (3afs